Islamization of Science Ismail Raji Al Faruqi in Forming Curriculum Integration at PTKI - Sutrisno Sutrisno (PT Publikasiku Academic Solution, 2023)
Islamic scholarship was born out of concern for modern Western science that deviated from the spirit of the Renaissance which initially aimed to humanize humans, instead, there was dehumanization and secularization. Islamic scholarship also intends to respond to the idea of the Islamization of science, which is seen as a textualization, that is, to make Western sciences in harmony with Islam. The objectives of this study is to: Know the biography of Ismail Raji Al Faruqi as a Muslim scholar; 2). Knowing the Islamization of Science Ismail Raji al-Faruqi; 3). Knowing the thoughts of Ismail Raji Al-Faruqi's Islamic education curriculum. Islam Ismail Raji Al-Faruqi (1921 – 1986 A.D.), was born in Jaffa, a city on the Palestinian coast (now Israel). Al-Faruqi was born on January 1, 1921, to a distinguished family and upheld the teachings of Islam, Al-Faruqi grew up in Palestine and inherited the strong character of the Palestinian Arab tradition that persistently fought for his nation to liberate it from Israeli occupation. So that his mind is firmly bound to Palestine and experiences firsthand the tragedy felt by the Palestinian people. Al-Farruqi, once a governor in Palestine, was also a visiting Professor in various countries, al-Faruqi had been educated in various countries, including Palestine itself, America, Canada Egypt al-Faraqi was killed in his home with his wife Louis Lamya and two children in 1986. Islamization is al-Faruqi's solution to change the education system in accordance with Islamic ideals that Muslims have long abandoned and the system and education system adopted by Muslims from the West is one that endangers the Islamic spirit by separating revelation from reason. The concept of the Islamic curriculum that Al-Faruqi wanted was a curriculum that developed the traditional system (Islam) and the modern system (West) by adjusting the vision of Islam. Al-Faruqi aims to blend both the Islamic system and the Western system and eliminate the shortcomings of both systems.